Reliability of Vestibular Perceptual Threshold Testing About the Yaw Axis. Issue 6 (November 2020) - Lee, Tiffany L.; Shayman, Corey S.; Oh, Yonghee; Peterka, Robert J.; Hullar, Timothy E.
Abstract : Objectives: Vestibular reflexes have traditionally formed the cornerstone of vestibular evaluation, but perceptual tests have recently gained attention for use in research studies and potential clinical applications. However, the unknown reliability of perceptual thresholds limits their current importance. This is addressed here by establishing the test-retest reliability of vestibular perceptual testing. Design: Perceptual detection thresholds to earth-vertical, yaw-axis rotations were collected in 15 young healthy people. Participants were tested at two time intervals (baseline, 5 to 14 days later) using an adaptive psychophysical procedure. Results: Thresholds to 1 Hz rotations ranged from 0.69 to 2.99°/s (mean: 1.49°/s; SD: 0.63). They demonstrated an excellent intraclass correlation (0.92; 95% confidence interval: 0.77 to 0.97) with a minimum detectable difference of 0.45°/s. Conclusions: The excellent test-retest reliability of perceptual vestibular testing supports its use as a research tool and motivates further exploration for its use as a novel clinical technique.